ATH700 : History of art and methodology / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2018)
This course discusses the different approaches in art history methodology beginning 15th century until the present day. These methodologies will include those of the Euro-American centric, the decolonization of methodologies and the Islamic art history methodology. It will enable students to develop a better understanding of the various methods in art history methodology. Students will be able to use these approaches in their Art History writings and researches.